Which index is the best to assess stream health? - Dos Santos, Daniel Andrés (2011)
Biotic indices are widely used in monitoring the health status of various ecosystems. The choice of the best index is generally done qualitatively depending on a variety of aspects including cost and time. ROC (Receiver Operating Characteristic) methodology constitutes a valuable tool to compare objectively the diagnostic capabilities of different tests in addition to obtain decision thresholds. In this manuscript, ROC methodology is described and implemented for the first time in the context of stream bioassessment through benthic macroinvertebrates. Cut-off values that distinguish impaired from healthy sites are suggested. A new index called IBY-4 is also developed. IBY-4 accounts for the occurrence of Megaloptera, Plecoptera, Trichoptera and Elmidae in a target site and may achieve the best general performance in the study region concerning to Andean Tropical streams.